1989
DOI: 10.1093/oxfordjournals.eurheartj.a059422
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency coagulation of ventricular myocardium: Improved prediction of lesion size by monitoring catheter tip temperature

Abstract: To assess the importance of voltage, current, impedance and catheter tip temperature for the prediction of the size of tissue injury induced by transcatheter radiofrequency application, radiofrequency pulses (500 kHz) were delivered both in vitro and in vivo to isolated ventricular preparations and the intact canine heart, respectively. Radiofrequency coagulations were performed using unipolar electrode configuration. Besides measurements of current and voltage which were used to calculate the delivered power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(40 citation statements)
references
References 0 publications
1
36
0
3
Order By: Relevance
“…In power-controlled ablation, increased tip temperature is associated with larger lesion dimensions, as illustrated by Hindricks et al 29 and Rosenbaum et al 13 This was also illustrated in those of our experiments in which power consumption approached the maximum generator output (pseudo-power-controlled ablation); in this group, reached tip temperature was positively correlated with lesion volume (Figures 2A and 4A). …”
Section: Lesion Volume Related To Average Delivered Power and Averagesupporting
confidence: 85%
“…In power-controlled ablation, increased tip temperature is associated with larger lesion dimensions, as illustrated by Hindricks et al 29 and Rosenbaum et al 13 This was also illustrated in those of our experiments in which power consumption approached the maximum generator output (pseudo-power-controlled ablation); in this group, reached tip temperature was positively correlated with lesion volume (Figures 2A and 4A). …”
Section: Lesion Volume Related To Average Delivered Power and Averagesupporting
confidence: 85%
“…[20][21][22] However, the rate of tissue temperature rise is progressively slower with increasing distance from the ablation electrode, 22,23 which limits the value of interface temperature measurement for monitoring deeper lesion growth. Recent experimental studies have suggested that the attenuation of the local electrical activity recorded from the ablating electrode may predict RF lesion formation.…”
mentioning
confidence: 99%
“…The mean number of applications of RF energy per patient was 5.9±3.3 (range: [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. There were no complications except for 1 patient with transient AV block.…”
Section: Clinical Resultsmentioning
confidence: 98%